Clinical Effects of Topical Application of Compound Betamethasone in Total Knee Arthroplasty - Sun, Xiaobo; Wang, Linjiao; Qin, Kai; Bai, Guoyang; Dou, Qunli (Journal of Contemporary Medical Practice, 2024)
Total knee replacement is the most effective treatment for end-stage knee osteoarthritis, and then postoperative pain becomes a major impediment to rapid patient recovery. Perioperative local infiltration analgesia has become an important part of multimodal analgesic management, but the combination of analgesic drugs among them is formulated with different standards. Many scholars have reported that glucocorticoids have favorable analgesic and anti-inflammatory effects in recent years. Compound betamethasone has been used as a potent, long-acting glucocorticoid in TKA. The purpose of this article is to review the efficacy of the localized application of compound betamethasone in total knee arthroplasty and to provide a reference for the clinical application of compound betamethasone.